Capital income taxation and the mirrlees review - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2012)
The Mirrlees Review of the UK tax system, together with its companion volume of research papers, can be expected to influence future discussions of tax reform. Indeed, this can already be recognised in the Henry Review. As far as income taxation is concerned, the most substantive recommendation of the Mirrlees Review is a move toward a system of consumption or expenditure taxation, by exempting the normal return to saving and taxing only excess returns on the same tax schedule as labour earnings. This paper argues against this direction of reform on the grounds that it is based on a model of household behaviour over the life cycle that ignores important aspects of reality. We present an alternative model, together with supporting empirical evidence. We go on to argue that, against the background of rising inequality and an aging population, the appropriate direction for reform is towards more progressive taxation of both labour earnings and capital income, although not necessarily under the same rate scale.
Keywords: H21; H24; H31; D13; D91; J22; 330; optimal taxation; labour supply; capital income taxation; family life cycle; time allocation; saving; inequality; Kapitalertragsteuer; Steuerreform; Optimale Besteuerung; Arbeitsangebot; Großbritannien